Penyusunan Laporan Keuangan Menurut SAK - EMKM pada Bengkel Rondang Service Medan - Epi, Yus; Arianto, Wahyu (Jurnal Perpajakan dan Akuntansi (JUPAK ), 2023)
Abstract— At present, the driving force for the development of economic growth is due to the existence of MSMEs (Micro, Small and Medium Enterprises) and Indonesian entrepreneurs. In the growth of the economy in Indonesia, it cannot be separated from the activities of entrepreneurs carried out individually or in groups. The trigger for the problems that exist in Micro, Small and Medium Enterprises is because entrepreneurs do not understand the preparation of good financial reports in accordance with SAK-EMKM (Financial Accounting Standards for Micro, Small and Medium Entities). They only make it as simple as only making bookkeeping on cash income and expenses, even though financial reports are the most important part of a business. lack of knowledge about how to make financial reports and the absence of training conducted by business owners in making good financial reports in accordance with the correct Accounting Standards. This study aims to assist Bengkel Rondang Service in preparing good financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM). In this study, researchers used descriptive and quantitative methods and researchers limited the research by taking data for 1 (one) month, namely December 2021. Then the primary data source obtained in the form of interviews and observations at the owner of the Rondang Service Workshop itself. From the results of this study, it shows that the financial statements at Bengkel Rondang Service are in the form of a statement of financial position or balance sheet, income statement and statement of changes in capital and notes on financial statements. This research is expected to be useful for Rondang Service Workshop in preparing good financial reports according to the Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM). Abstrak— Pada masa saat ini pendorong berkembangnya pertumbuhan ekonomi disebabkan oleh adanya para UMKM (Usaha Mikro Kecil Menengah) serta para pengusaha Indonesia. Dalam pertumbuhan perekonomian di Indonesia tidak terlepas dari para kegiatan para wirausahaan yang dilakukan secara individu maupun kelompok. Pemicu terjadinya permasalahan yang ada pada pada Usaha Mikro kecil Menengah adalah disebabkan karna para wirausahaan belum mengerti dalam pembuatan laporan keuangan yang baik sesuai dengan SAK-EMKM ( Standart Akuntansi Keuangan Entitas Mikro Kecil dan Menengah ). Mereka hanya membuat seadanya saja seperti hanya membuat pembukuan pada pendapatan dan pengeluaran kas itu saja, padahal laporan keuangan bagian terpenting dalam suatu usaha. kurangnya ilmu pengetahuan tentang cara pembuatan laporan keuangan serta tiadanya pelatihan yang dilakukan oleh para pemilik usaha dalam pembuatan laporan keuangan yang baik sesuai dengan Standart Akuntansi yang benar. Penelitian ini bertujuan membantu Bengkel Rondang Service dalam penyusunan laporan keuangan yang baik sesuai dengan Standart Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK-EMKM). Pada penelitian ini peneliti menggunakan metode deskriptif dan kuantitatif serta peneliti membatasi penelitian dengan mengambil data selama 1 ( satu ) bulan yaitu desember 2021. Kemudian sumber data primer yang didapat dalam bentuk wawancara dan Observasi pada pemilik Bengkel Rondang Service sendiri. Dari hasil penelitian ini menunjukkan laporan keuangan pada Bengkel Rondang Service dalam bentuk laporan posisi keuangan atau neraca, laporan laba rugi dan laporan perubahan modal serta catatan pada laporan keuangan. Penelitian ini diharapkan dapat bermamfaat bagi Bengkel Rondang Service dalam Penyusunan laporan keuangan yang baik sesuai Standart Akuntansi Keuangan Entitas Mikro Kcil dan Menengah (SAK-EMKM).